A state-of-the-art review on mechanical performance characterization and modelling of high-performance textile reinforced concretes. (12th September 2022) - Rawat, Prashant; Liu, Sai; Guo, Shuaicheng; Zillur Rahman, Md; Yang, Ting; Bai, Xiayang; Yao, Yiming; Mobasher, Barzin; Zhu, Deju
Highlights: A detailed discussion on the constituents and design parameters of TRC is presented. The mechanical properties of TRC are critically reviewed under various loading conditions. The fracture mechanisms and modes under different loadings are discussed. The outcome of the review highlights the research gap and perspective of TRC. Abstract: Textile reinforced concrete (TRC) is becoming an emerging high-performance construction material due to its outstanding load-bearing capacity, corrosion resistance, and durability. However, the influences of textile type and design parameters on the mechanical performance of TRC have not been fully understood. Therefore, this study aims to enhance the understanding of the mechanical performance of TRC and identify further research needs. The tensile, compressive, and flexural performances of TRC are first discussed based on the literature review. It is found that the mechanical properties of TRC are highly dependent on the shape, geometry, woven type, and yarn properties of the textile. The failure patterns of TRC under tensile and flexural loadings generally include three stages: linear elastic (before the first crack), strain hardening (with multiple cracking), and softening (with fracture failure). The bonding performance of the textile embedded in the cementitious matrix is also reviewed using the pullout test results. The geometric parameters and surface characteristics of the textile significantly affect the interfacial bonding strength. Currently, the analytical models for the mechanical analysis of TRC and the numerical analysis for the 2D and 3D textile-reinforced concrete are available to predict their mechanical behaviours. This study can provide a valuable reference for further investigations on TRC materials and promote their applications in civil engineering.